Konseling Klasikal Berbantuan Musikalisasi dalam Mengatasi Perilaku Bullying - Anjelli Nur Aisyah; Kusnadi Kusnadi (Scidacplus, 2025)
Bullying behavior has become a serious issue among children, especially in the educational environment. Bullying is an aggressive behavior that is repeatedly carried out with the intention of harming or intimidating others, leading to negative impacts on both the victim and the perpetrator. The consequences can be severe, ranging from discomfort and insecurity to deep trauma. Therefore, appropriate solutions are needed to reduce bullying behavior among children. Classical counseling assisted by musicalization is a creative solution to address this issue. This study, titled